Need to promote healthy lifestyle as primary prevention to the COVID-19 and to improve the immune response to vaccines - De la Cámara, Miguel Á; Pardos-Sevilla, Ana I; Jiménez-Fuente, Augusto; Veiga, Óscar L (Acta Biomedica Atenei Parmensis, 2020)
Letter to the editor